Reflections on the application of the english law’s model of constructive trusts to the handling of specific property relations in vietnamese legal practice (Jurnal Cita Hukum, 2025)
Contemporary Vietnamese legal practice recognizes numerous complex scenarios concerning property relations, wherein the pursuit of equitable outcomes cannot be readily achieved through the straightforward application of existing legal provisions.  Two categories of cases have recently garnered significant attention from both the media and the public.  The first involves the mistaken transfer of funds into another individual’s bank account; the second concerns the recovery of assets by the State from individuals convicted of corruption-related offences.  English law provides the mechanism of the trust—more specifically, the constructive trust—as a legal remedy to address such issues.  Accordingly, there is scope to study and potentially incorporate the experience of English law to enhance Vietnam’s legal framework governing property relations arising in these contexts.